2020
DOI: 10.1177/0300060520949409
|View full text |Cite
|
Sign up to set email alerts
|

Association of −344C/T polymorphism in the aldosterone synthase (CYP11B2) gene with cardiac and cerebrovascular events in Chinese patients with hypertension

Abstract: Objective Several recent studies have shown that the aldosterone synthase gene ( CYP11B2) −344C/T polymorphism is related to cardiovascular diseases. However, whether the −344C allele influences the incidence of cardiovascular diseases in Chinese patients with hypertension is unclear. Methods Chinese patients with essential hypertension were genotyped for the −344C/T polymorphism in CYP11B2 (n = 755; CC, n = 112; CT, n = 361; TT, n = 282) and followed for 11 years for major adverse cardiovascular events (MACEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…A study by Wang et al . [ 47 ] conducted in China investigated hypertensive patients and showed that the CYP11B2-344 CC genotype was an independent risk factor for coronary artery disease and stroke. [ 47 ] In contrast, Pi et al .…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Wang et al . [ 47 ] conducted in China investigated hypertensive patients and showed that the CYP11B2-344 CC genotype was an independent risk factor for coronary artery disease and stroke. [ 47 ] In contrast, Pi et al .…”
Section: R Esultsmentioning
confidence: 99%
“…[ 47 ] conducted in China investigated hypertensive patients and showed that the CYP11B2-344 CC genotype was an independent risk factor for coronary artery disease and stroke. [ 47 ] In contrast, Pi et al . [ 48 ] conducted a meta-analysis in 2013 to investigate genetic susceptibility to ischemic stroke using the 344C/T polymorphism of the CYP11B2 gene, and their results did not find any relationship between the two.…”
Section: R Esultsmentioning
confidence: 99%
“…The CYP11B2 gene (located on chromosome 8q24.3) encodes aldosterone synthetase (ALDOS) and is regulated by angiotensin II. Several recent studies have shown that the CYP11B2 gene rs1799998 -344C/T polymorphism is correlated with the presence of cardiovascular disease (CVD) [ 117 , 118 ]. A meta-analysis by Wang et al [ 118 ] showed that the allelic variant 344CC is a risk factor for CAD and ischemic stroke in the Chinese population [ 118 ].…”
Section: Polygenic Cad: Genes and Polymorphisms Associated With Cadmentioning
confidence: 99%
“…Several recent studies have shown that the CYP11B2 gene rs1799998 -344C/T polymorphism is correlated with the presence of cardiovascular disease (CVD) [ 117 , 118 ]. A meta-analysis by Wang et al [ 118 ] showed that the allelic variant 344CC is a risk factor for CAD and ischemic stroke in the Chinese population [ 118 ]. The presence of the CYP11B2 -344C allele was associated with an increased risk of MI in smokers and those with dyslipidemia in a Finnish study [ 119 ].…”
Section: Polygenic Cad: Genes and Polymorphisms Associated With Cadmentioning
confidence: 99%
“…В китайском исследовании с участием пациентов с артериальной гипертензией, Wang L и соавт. показали что CYP11B2 -344 CC генотип был независимым фактором риска ИБС и инсульта [40].…”
Section: клиническая фармакогенетикаunclassified